The Dynamics of Personal Branding on Instagram: A Case Study of Prilly Latuconsina's Advocacy for Independent Women - Ronnfeld, Sylvia Alexandra; Bernadette, Sophia (Yayasan Ilomata, 2025)
This study examines the role of Instagram in shaping and promoting the image of independent women through the personal branding strategies employed by Prilly Latuconsina. Using a qualitative research methods that elaborate the purposive sampling which is the followers of Prilly Latuconsina to provide a more targeted and specific sample to answer research question. This research analyzes Latuconsina’s Instagram account, @Prillylatuconsina96, based on Rampersad’s 11 Characteristics of Personal Branding. The research employed a triangulated data collection approach, incorporating content analysis of posts, stories, and audience engagement, along with qualitative interviews with social media experts and followers. The findings reveal that Latuconsina effectively applies the principles of authenticity, consistency, visibility, and differentiation in constructing her personal brand. She utilizes visually compelling content and active audience engagement to reinforce messages of empowerment and independence. By showcasing her career journey, achievements, and personal insights, Latuconsina successfully establishes a credible and inspiring personal brand. Building on Hubert K. Rampersad’s concept of personal branding, this research highlights the crucial role of authenticity, consistency, and value alignment in shaping an individual’s digital presence. By examining Instagram’s effectiveness as a platform for influencing public perception and driving societal change, the study reinforces the significance of long-term brand consistency in strengthening the image of independent women. In line with Rampersad’s emphasis on strategic personal brand development, the findings offer valuable insights for individuals and professionals seeking to harness social media as a powerful tool for cultivating an authentic, credible, and influential personal brand.